An overview of energy minerals in the Springbok Flatsbasin, South Africa : implications for geochemical and geophysical exploration - Ledwaba, Lebogang John (Rhodes University, Faculty of Science, Department of Geology, 2015)
This study is informed by the rising demand for power needs in South Africa and aims at understanding the geophysical and geochemical characteristics of the energy minerals in the Springbok Flats Basin and relating them to the prevailing geological and structural setting for improved exploration targeting. The Springbok Flats Basin is part of the Karoo sediments and host to uranium, coal and coal bed methane (CBM) resources. The lithology sections in the basin indicate presence of basaltic lavas at the top, underlain by mudrocks, siltstones, sandstones, conglomerates and diamictite, with interbedded coal beds occasionally. The coals are uraniferous and shale bounded and of lower Beaufort age at 250 Ma. The regional radiometric data identifies the regional extent of the Springbok Flats Basin as a basin with low total count values. This information is useful in exploration as it gives an idea of the limits of the area where to focus application for prospecting licenses. The reduced to pole of the total magnetic field, residuals and first vertical derivative maps clearly show the high magnetic susceptibility nature of the surrounding Bushveld rocks as compared to the low Karoo sediment susceptibility within the basin. There are distinct ring shaped picks within the basin possibly due to known Karoo dolerite sills in particular to the central south western part of the grid. The regional geochemical mapping program is a cost-effective way of providing an overview of the relative abundance levels, regional trends and anomalous patterns in the underlying lithological units. Background values of elements in soils over different lithological units and the identification of anomalous values relative to these elements can easily be identified. The geochemical results show an excellent correlation between soil chemistry and underlying geological formations. A few distinct gravity highs are clearly shown within the basin. Assuming the effect of the Letaba basalt to the gravity readings is uniform across the basin; these distinct anomalies could be due to Karoo dolerite sills as they coincide with areas of distinct high magnetic signature. A conceptual model was generated assuming that the Karoo sediments' layering is uniform across the gravity profile but changes in the residual are due to an increased thickness of the sill supported by the gentle changes on the surface topography. Satellite imagery has got its challenges especially in areas of vegetation but it does provide a very useful tool in exploration. A number of spectral analysis techniques and band rations can be used to differentiate the areas underlain by the Letaba basalts, the Karoo sandstones/shale and Bushveld granites for mapping purposes. The priority focus will be on the shallower Karoo sediments because of the potential for cheaper mining. Exploration targeting needs to be guided by observed geochemical and geophysical characteristics in order to prioritize areas taking into account the presence of Karoo intrusives such as the dolerite sills that tend to devolatize the coal hence affecting the quality/rank. Structures and gravity signatures are very important in delineating areas with thick sediments that have a potential for CBM. The same understanding in targeting goes a long way in planning drill holes, resource modelling and pre-feasibility stages for mine planning. A high resolution airborne geophysical survey is recommended over the basin to better resolve structures. Geophysical borehole logging is recommended to be part of the exploration drilling programs in the Springbok Flats Basin in order to define the in-situ geophysical characteristics. Geophysical logging is useful in particular for the uranium reserves that cannot be delineated from the surface due to deep intersection.
Keywords: Energy minerals -- South Africa -- Springbok Flats (Limpopo); Geochemistry; Prospecting -- Geophysical methods; Coal -- South Africa -- Springbok Flats (Limpopo); Uranium -- South Africa -- Springbok Flats (Limpopo); Coalbed methane -- South Africa -- Springbok Flats (Limpopo)